Lexicons in Cendrawasih Dance at Buleleng - Sacani, Ketut Catur Arya; Ramendra, Dewa Putu (Universitas Pendidikan Ganesha, 2022)
The Cendrawasih dance typical Buleleng is a traditional Balinese dance from Buleleng, Bali. This dance has lexicons that can be found in its dance movements. However the Cendrawasih Dance at Buleleng is not widely known and has almost been forgotten, in addition it has been re-enacted. Furthermore, during dance practice, dancers changed some of the lexicons from Balinese to Indonesian. If these lexicons that use Balinese are rarely used , the language will experience extinction, and Balinese culture will be lost. Documenting and capturing the culture is one way to save it from extinction. This study aims to analyze the lexicons based on movements in Cendrawasih dance at Buleleng, along with the cultural meaning of the lexicons. This study was descriptive qualitative research using an ecolinguistics approach. The data were obtained through observation and interviews. The description of the lexicons that has been obtained was translated into English and then described. After that, lexicons that have cultural meanings will be described. The result found there are 26 lexicons related to the dance movements of Cendrawasih Buleleng. The lexicons are categorized into five types part of body movements, such as three lexicons in head movements, three lexicons in eye movements, nine lexicons in hand movements, nine lexicons in leg movements, and two lexicons in body movements. There are ten lexicons that have cultural meanings.